Effect of Praying Meditation: "God in a breath" on Reducing Blood Pressure in Hypertension Patients - Melkias Dikson; Agustina Sisilia Wati Dua Wida; Fransiska Aloysia Mukin (Media Karya Kesehatan, 2021)
Hypertension is a disease called the silent killer because the symptoms are without complaint, only known after complications are discovered. Increased blood pressure in patients with hypertension can be overcome by using pharmacological and non-pharmacological treatments. Non-pharmacological therapy that can be done to reduce blood pressure in hypertensive sufferers is stress management using meditation therapy. Praying Meditation: "God In A Breath". This study aims to determine the effect of Praying Meditation: "God In A Breath" on reducing blood pressure in patients with hypertension. This research was conducted in the working area of Puskesmas Koting District, Sikka Regency. This study used a quasi experimental design with a randomized pretest-posttest control group design approach, the study sample used a simple random sampling of 87 people. The analysis used univariate with frequency and percentage, bivariate using the Wilcoxon test, and statistical difference test (Mann-Whitney test). The results showed that the Wilcoxon test had a significant effect on the Praying Meditation: "God In A Breath" intervention on blood pressure with a p-value of 0.000 (<0.05). The results of the Mann-Whitney test showed a significant difference between the blood pressure of the intervention group and the control group with a p-value of 0.000 (<0.05). Prayer meditation has an effect on lowering blood pressure so that it can be one of the nursing interventions that can be given by nurses and can be continued by hypertensive patients independently. Keywords: blood pressure,hypertension , praying meditation.